2015
DOI: 10.1016/j.ijid.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Directed shift of vaginal microbiota induced by vaginal application of sucrose gel in rhesus macaques

Abstract: Rhesus macaques can be used as animal models of bacterial vaginosis to develop drugs and test treatment efficacy. Furthermore, the topical application of sucrose gel induced the shifting of vaginal flora of rhesus macaques from a BV kind of flora to a lactobacilli-dominating flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
(13 reference statements)
2
17
2
Order By: Relevance
“…In addition to these shared functions, the core genome of L. crispatus also includes the enzymes necessary to ferment lactose, galactose, fructose, and sucrose. A previous study showed that the application of a sucrose gel can select for L. crispatus in the Rhesus macaque vagina (62), lending credence to this result. Furthermore, fructose can be found in high abundance in male ejaculate (63).…”
Section: Discussionsupporting
confidence: 55%
“…In addition to these shared functions, the core genome of L. crispatus also includes the enzymes necessary to ferment lactose, galactose, fructose, and sucrose. A previous study showed that the application of a sucrose gel can select for L. crispatus in the Rhesus macaque vagina (62), lending credence to this result. Furthermore, fructose can be found in high abundance in male ejaculate (63).…”
Section: Discussionsupporting
confidence: 55%
“…Detailed analysis of the pigtail macaque vaginal microbiome has been reported resulting in preferred use of this species in microbicide studies . RM and particularly CM vaginal environments have received comparatively less attention, even though both species are used extensively for the testing of vaccine efficacy, including protection from repeated vaginal challenges . Moreover, the ability to colonize macaques with Lactobacilli to mimic a healthy human vaginal environment has not systematically been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent article utilizing DNA‐based sequencing reported that only 4 of 11 rhesus macaques had Lactobacillus sequences (Spear et al, ). Another study employing 16S rRNA sequencing found that Lactobacillus represented less than 2% of sequences in the vaginal specimens from 16 rhesus monkeys (Hu et al, ). These results are in marked contrast to the healthy profile for women, in whom Lactobacilli are typically the dominant taxa (Ravel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have taken advantage of this bacterial attribute of the monkey reproductive tract to investigate clinical treatments for changing the commensal bacteria (Scorpio, Ruben, Liao, Hildreth, & Fletcher, ). Even in female rhesus monkeys, topical introduction of a sucrose gel vaginally for just 5 days markedly increased Lactobacilli , and decreased Porphyromonas, Sneathia , and Mobiluncus , and changed the acidity of their CVF (Hu et al, ). It has also been possible to colonize the reproductive tract of rhesus monkeys with recombinant Lactobacillus jensenii expressing an antiviral protein, which afforded protection against retroviral infection (Lagenaur et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation